Pengelolaan Google Classroom dalam Hasil Belajar Siswa - Pratama, Surya Adi; Hamengkubuwono, Hamengkubuwono; Kusen, Kusen; Warlizasusi, Jumira (JOEAI (Journal of Education and Instruction), 2022)
This study aims to explain effectiveness in managing google classroom and its obstacles, and describe learning outcomes in managing google classroom. This research uses a qualitative approach with a descriptive type. The research results show that the management of google classroom runs quite effectively in the learning process because students are more active and enthusiastic about using google classroom during the learning process. The obstacles in managing Google Classroom include that there are still students who don't have an Android cellphone, have difficulty buying internet quota and for students who live far from the city have difficulty getting an internet signal. Learning outcomes obtained in the collection of student assignments. Teachers and students must be active in Google Classroom and students can collect assignments through photos or documents then the teacher can immediately give grades so that students can find out the results of assignment scores that have been collected through Google Classroom. In conclusion, the management of google classroom as a learning tool runs quite effectively, teachers and students can use google classroom as an alternative to online learning, even though there are some drawbacks and obstacles such as quota availability, signal problems and cellphone misuse. Keywords: Google classroom, Learning Outcomes, Management